Inteligência emocional como habilidade protetiva à saúde mental de estudantes da educação especial no Ensino Superior - Brum, John Leimar Matheus (2025)
This dissertation investigated the relationship between mental health, emotional intelligence, and academic performance of special education students in higher education. The inclusion of this group represents significant progress but is still marked by emotional, pedagogical, and institutional challenges that may compromise persistence and learning. In this context, emotional intelligence was considered a protective skill that supports students in coping with academic and emotional difficulties. The general objective was to know the relationship between mental health and emotional intelligence in the academic performance of special education students in higher education. The specific objectives were: to analyze the role of mental health and emotional intelligence in the development of students’ learning skills; to identify the main emotional difficulties that impact students’ academic performance; and to present interventions based on the development of emotional intelligence and support for mental health to improve academic performance. The research adopted a mixed-methods approach, combining qualitative and quantitative procedures. Data were collected through a structured questionnaire with 25 open and closed questions, applied to special education students at the Federal University of Santa Maria (UFSM). The responses were analyzed statistically and interpreted through Content Analysis (BARDIN, 2011), which made it possible both to measure levels of emotional intelligence and mental health and to deepen the understanding of emotional experiences, regulation strategies, and perceptions of institutional support. The results showed that difficulties such as anxiety, loneliness, course failures, and barriers to socialization significantly affect mental health and academic performance. It was found that emotional intelligence skills—such as self-awareness, self-regulation, empathy, and motivation—function as protective factors, although they still require stronger institutional reinforcement. Among the highlighted proposals were the expansion of psychological support, the reduction of academic bureaucracy, and the creation of inclusive socialization spaces. It is concluded that the development of emotional intelligence can strengthen both mental health and academic persistence, functioning as an essential preventive strategy. The findings provide relevant insights for the development of institutional policies that are more sensitive to the emotional demands of special education students, reinforcing the importance of building an inclusive, welcoming, and holistic university environment.